2012
DOI: 10.1038/hr.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Carotid cross-sectional wall area is significantly associated with serum leptin levels, independent of body mass index: the SABPA study

Abstract: Hypertension and obesity are serious health burdens in sub-Saharan Africa. Urbanized Africans seem to be more susceptible to the development of these diseases than Caucasians. Current research suggests that leptin may be an important contributor to the development of hypertension and atherosclerosis. The aim of this study was to investigate leptin levels and their associations with cardiovascular function in urbanized Africans and Caucasians. Serum leptin, ambulatory blood pressure and carotid intima-media thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
2
12
0
2
Order By: Relevance
“…There was no interaction of ethnicity (Table ) between our variables of interest with leptin, but to further strengthen our findings and based on a previous study that has showed differences in leptin levels based on ethnicity, we also divided the subjects based on sex and ethnicity (Table ). Again, both the black and white men showed a negative association between CIMT (black men, Std β = −0.29; P = 0.034; R 2 = 0.08; white men, Std β = −0.24; P = 0.042; R 2 = 0.07) and CSWA (black men, Std β = −0.22; P = 0.038; R 2 = 0.10; white men, Std β = −0.25; P = 0.022; R 2 = 0.08) with leptin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no interaction of ethnicity (Table ) between our variables of interest with leptin, but to further strengthen our findings and based on a previous study that has showed differences in leptin levels based on ethnicity, we also divided the subjects based on sex and ethnicity (Table ). Again, both the black and white men showed a negative association between CIMT (black men, Std β = −0.29; P = 0.034; R 2 = 0.08; white men, Std β = −0.24; P = 0.042; R 2 = 0.07) and CSWA (black men, Std β = −0.22; P = 0.038; R 2 = 0.10; white men, Std β = −0.25; P = 0.022; R 2 = 0.08) with leptin.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of leptin's receptor within the vasculature also laid credence for leptin's involvement in the regulation of vascular function which itself has yielded conflicting reports . For example, leptin was shown to predict atherosclerosis, stroke, myocardial infarction and also coronary events in either overweight or obese individuals . In contrast, other studies have reported a vascular protective role of leptin against atherosclerosis in either overweight or obese humans or animals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании NAS (Normotensive Aging Study) было показано, что с увеличением ИМТ и окружности талии повышается экскреция норадреналина с мочой. Повышение симпатических влияний также при-водит к увеличению секреции ренина почками [30].…”
Section: Resistant Hypertension резистентная артериальная гипертензияunclassified
“…В свою очередь повышенный уровень альдостеро-на плазмы является значимым фактором риска мета-болического синдрома [11]. Снижение веса у больных ожирением ведет к снижению концентрации альдо-стерона в плазме.…”
Section: особенности диагностики резистентной артериальной гипертензииunclassified